Exploring the plastome diversity of fifteen centuries-old olive trees (Oleae europaea L.) from Jordan: insights and implications for conservation - D’Agostino, Nunzio; Fruggiero, Ivan; Maisto, Alessandro; Taranto, Francesca; Al-Kilani, Mazen A.; Al-Abdallat, Ayed M. (Frontiers in Plant Science, 2025)
The olive tree (Olea europaea L.) holds exceptional ecological, cultural, and economic significance in the Mediterranean Basin. Understanding its genetic diversity is critical for conservation, breeding, and authentication of olive cultivars. While nuclear genome analyses have elucidated much of the species’ genetic structure, chloroplast genome sequencing provides complementary insights, particularly in tracing maternal lineages, uncovering domestication pathways, and identifying cryptic genetic variation. In this study, we investigated the plastome diversity of fifteen centuries-old olive trees from Jordan through reference-guided assembly and comparative analysis using the FARGA cultivar plastome as a reference. Despite overall genomic conservation, nucleotide diversity analyses revealed several polymorphic hotspots—most notably within the psbM and ycf1 genes and the atpB-rbcL intergenic spacer. Structural variation, including simple sequence repeats and tandem repeats, highlighted intra-population diversity. One sample (TF - 3) exhibited heteroplasmy, suggesting a biological origin that warrants further investigation. Phylogenetic reconstruction grouped most samples within the Mediterranean E1 lineage, with TF - 3 and a few others forming distinct clusters. Comparisons with nuclear genotyping data demonstrated both congruence and divergence, emphasizing the value of a dual-genome approach. This study reinforces the utility of plastome sequencing in varietal identification, conservation genetics, and evolutionary studies, and contributes novel genomic resources for Jordanian olive germplasm.